2012
DOI: 10.4236/fns.2012.311204
|View full text |Cite
|
Sign up to set email alerts
|

Sanitation Practices among Food Handlers in a Military Food Service Institution, Malaysia

Abstract: This study was conducted over a period of two months to assess the food hygiene practices among food handlers in a military food service institution that have been trained with food safety practices and knowledge. Since limited data was published for the services rendered to governmental agencies such as the military, this study was conducted to determine the level of knowledge, attitude and motivation of food handlers under this institution that was responsible for the provision of food to the armed forces in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 17 publications
0
18
1
Order By: Relevance
“…Besides, having sufficient knowledge on temperature control has also been identified as a motivator for food handlers to perform the practices. Provision of knowledge or training have been widely reported in previous studies to be able to motivate food handlers to perform correct food safety practices (Lee et al, 2012;Thaivalappil et al, 2018).…”
Section: Motivators To Perform Proper Temperature Control Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Besides, having sufficient knowledge on temperature control has also been identified as a motivator for food handlers to perform the practices. Provision of knowledge or training have been widely reported in previous studies to be able to motivate food handlers to perform correct food safety practices (Lee et al, 2012;Thaivalappil et al, 2018).…”
Section: Motivators To Perform Proper Temperature Control Practicementioning
confidence: 99%
“…This risk factor is also evident in Malaysia, whereby besides improper food handling and poor personal hygiene, temperature abuse has been identified as one of the causative factors for foodborne outbreaks (Sharifa et al, 2013;Abdul-Mutalib et al, 2015). Deficiency of temperature control was clearly shown in a study by Lee et al (2012), where end-point cooking temperatures were not consistently recorded, and cold foods were frequently found to be above the recommended 5°C. In a study to assess food temperature and holding time among cafeterias in UiTM, Terengganu, it was found that three out of four cafeterias were not in compliance with temperature control guidelines, and food was found to be displayed at a tray line without proper holding equipment (Musa et al, eISSN: 2550-2166 © 2020 The Authors.…”
Section: Introductionmentioning
confidence: 99%
“…Food poisoning and contamination has become a major issue in our public institutions, with so many incidences being reported and some still in the hidden by food consumers. Hygiene practices covers proper acquisition and storage of food items, maintenance of clean environment during food preparation and serving, and assurance that all equipment and serving dishes are clean/ free from pathogens and further contaminants (Lee, Chik, Baka, Saari, & Mahyudin, 2012). Food safety plays a significant role in the economic and health development of Nations by safeguarding the nation's health, enhancing tourism, hospitality and international trade, the production, distribution and consumption of safe food (Tansey & Worsley, 2014).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The hygiene practice itself include the proper stage in ICOHS 2017 preparing food items, maintenance of creating clean environment, especially for food preparation and assurance of all the food being served in clean and free of bacteria condition [15]. The bacteria has a big potential in causing some food borne illnesses [15].…”
Section: Introductionmentioning
confidence: 99%
“…According to Food and Agriculture Organization (FAO), good hygiene practices can be described as all practices that related to the conditions which is necessary to ensure the safety and the suitability of the food in each stage of the food making process [11]. The hygiene practice itself include the proper stage in ICOHS 2017 preparing food items, maintenance of creating clean environment, especially for food preparation and assurance of all the food being served in clean and free of bacteria condition [15]. The bacteria has a big potential in causing some food borne illnesses [15].…”
Section: Introductionmentioning
confidence: 99%